2013
DOI: 10.4236/aces.2013.33026
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Morphological Properties of Polypropylene/Polyoxymethylene Blends

Abstract: This work studies the mechanical and morphological properties of polypropylene (PP)/polyoxymethylene (POM) blends. The PP/POM blends were prepared by melting-blend with an internal mixer. The contents of PP were used at 10%, 20%, 30%, 70%, 80% and 90% by weight. The phase morphology of the blends was observed by scanning electron microscope (SEM) due to the mechanical properties depended on the phase morphology. The results show the decrease of the impact strength, Young's modulus and tensile strength of POM/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 7 publications
(8 reference statements)
1
17
0
Order By: Relevance
“…Polymer blending is a convenient and efficient method to produce new materials that can combine the excellent properties of more than one component. An advantage of polymeric blends is the possibility to achieve a wide range of properties by adjusting the ratio of the components in the blend and the processing conditions . However, this is not a straight forward technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer blending is a convenient and efficient method to produce new materials that can combine the excellent properties of more than one component. An advantage of polymeric blends is the possibility to achieve a wide range of properties by adjusting the ratio of the components in the blend and the processing conditions . However, this is not a straight forward technique.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain a blend with tailored properties, some level of compatibility must exist between the polymer pairs. Specifically, a synergistic effect among the components is required to obtain improved properties with respect to the neat resins …”
Section: Introductionmentioning
confidence: 99%
“…The formed voids are quite different in shape compared with the voids observed by Jose et al in the case of immiscible blends of PP and HDPE . There is no sign of phase separation or formation of sphere‐shaped voids such as shown in the case of compatibilized polymer blends, which suggest that PS became an integral part of the HDPE polymer.…”
Section: Resultsmentioning
confidence: 60%
“…The XRD patterns showed that the interlayer spacing of the intercalated phase increased from 6.15 to 11.18 Ǻ indicating that the polymer was inserted into the MoS 2 galleries. The effect of Al 2 O 3 on mechanical and morphological properties of POM/Al 2 O 3 nanocomposites was investigated by Wacharawichanant et al (2011). Next, POM/ MoS 2 nanoballs composite was prepared and compared with POM/micro-MoS 2 composite.…”
Section: Pom/inorganic Oxides and Salts Nanocompositesmentioning
confidence: 99%